Analysis of the Surakarta Palace as a Historical Tourist Spot and Its Role in the Present (Historical and Descriptive Studies) - Laelly Qodariah; Arum Fatayan; Fitri Nur Aini; Aksal Firmansyah; Siti Roudotul Fadillah (UIN Sumatera Utara Medan, 2022)
Keraton Surakarta is a historical tourist attraction as well as cultural preservation which until now still exists and has not been lost by civilization. Keraton Surakarta adheres to the acculturation of culture from the time of their ancestors. Until now, the Surakarta Palace has been led by 12 kings, starting from Paku Buwono II to the king who is currently on the throne of the Surakarta Palace, Paku Buwono XIII. This study will explain the history, culture, and influence of the Surakarta palace in the present. The method used is a qualitative method with a historical and descriptive approach with four stages, namely: Heuristics, Source Criticism, Interpretation, and Word Historiography as well as data triangulation and data reduction. The Surakarta Palace is one of the historical heritages in Indonesia. In addition, the efforts made by the palace to introduce the life and heritage of the palace to the public, in this case tourists, are a public historical activity. Public history activities basically reflect the fighting spirit to keep trying to be able to return historical ownership to the general public.